Paradigma Pendidikan Islam Transformatif dalam Pemikiran Abdurrahman Wahid: Integrasi Epistemologi, Spiritualitas, dan Keadilan Sosial - Chandra, Widyawati; Ulum, Muhammad Babul (HUMANIKA, 2025)
Islamic Education in Indonesia has long been trapped in a dichotomy between religious sciences and secular sciences, coupled with a technocratic tendency that reduces its spiritual dimension and liberative Islamic values. This article presents a philosophical inquiry into the paradigm of transformative Islamic education, drawing on the thought of Abdurrahman Wahid (Gus Dur). Employing a qualitative approach —comprising library research and interpretative philosophical analysis — this study elaborates on the ontological, epistemological, and axiological foundations of Gus Dur’s transformative education. The findings reveal that Gus Dur situates religious rationality as the epistemological basis that integrates reason, revelation, and historical experience. Education, in his perspective, is not merely the transmission of information but an emancipatory praxis that harmoniously cultivates intellectual, moral, and spiritual dimensions—leading to the formation of human beings who are humanistic, inclusive, and committed to social justice. This article further presents curricular, pedagogical, and policy implications for implementing a transformative model within the contexts of pesantren, madrasah, and Islamic higher education.